(untitled) (Fiep Bulletin - online, 2011)
This work researches about the conceptual relations of leisure and ludic in the university through the debate that has the purpose of fixing extension politics connected with leisure. It’s permeated by a dialogue that understands leisure as a cultural product which is historically built as a pleasure human dimension, personal satisfaction. The research context was the State University of Mato Grosso (UNEMAT), Campus Universitário of Sinop City located in Brazilian Amazon. The methodology is drawn into the qualitative research and based on the ethnographic educational framework which suggests an immersion in the research cultural universe. It has documents analysis and in-depth interviews as methods. The interviews were done with teachers that work in extension projects that has leisure as object, students of the university and local community. The social actors were worth instruments to understand the value for leisure as a cultural phenomenon joined to the human ludic way which promoted the human development. Contemporary authors’ theories Dumazedier, Josep Puig, Jaume Trilla, Nelson Marcelino, Silvino Santin, Paul Lafargue e Bertrand Russel and some others – were used for the basis of the research. The results presented here do not finish in their own but point to the collaboration of these written document in order to a critic re-thinking to the knowledge production about leisure to stimulate discussions around the blanks, fundamental action to improve the studies and qualified interventions towards Education, Culture and Society areas to allow leisure – university – society exists through an extension politics: continuing, joint and dialogic politics.